2014
DOI: 10.1002/wcs.1300
|View full text |Cite
|
Sign up to set email alerts
|

Cultural context of cognitive development

Abstract: The authors have declared no conflicts of interest for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Many of these children have no consistent access to high-quality schooling and thus are considered to be lacking in academic knowledge. However, studies have shown that children develop rich forms of mathematical knowledge through participation in out-of-school activities, pointing to the close link between cognitive development and sociocultural context (Nasir, 2000;Saxe, 1991;Saxe & De Kirby, 2014;Sitabkhan, 2009). This line of research has revealed a good deal about children's mathematical development through everyday activities, but the development of their economic concepts remains a significantly understudied area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these children have no consistent access to high-quality schooling and thus are considered to be lacking in academic knowledge. However, studies have shown that children develop rich forms of mathematical knowledge through participation in out-of-school activities, pointing to the close link between cognitive development and sociocultural context (Nasir, 2000;Saxe, 1991;Saxe & De Kirby, 2014;Sitabkhan, 2009). This line of research has revealed a good deal about children's mathematical development through everyday activities, but the development of their economic concepts remains a significantly understudied area.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of this literature, Saxe and De Kirby (2014) discussed two alternate approaches to the study of culture and cognitive development. In the first, "dichotomous approach," culture and cognitive development are treated as two separate variables, where measures of cognitive development, such as IQ tests or standardized testing, are explained by cultural factors, such as socioeconomic status, levels of poverty, and parental involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Partition dependence, due to its nature as a cognitive phenomenon, may vary between different populations. Many aspects of cognition including memory, reasoning, and intelligence develop as people age from infants to older adults, as well as change due to life experiences (Saxe & de Kirby, 2014). However, most partition dependence studies have been conducted with college-aged students.…”
Section: Developmental Change and Special Populationsmentioning
confidence: 99%